Association Between Funisitis and Childhood Intellectual Development: A Prospective Cohort Study - Liu, Chengbo; Chen, Yan; Zhao, Dongying; Zhang, Jun; Zhang, Yongjun (Frontiers in Neurology, 2019)
Background: Previous studies have suggested that prenatal inflammation could damage the immature brain of preterm infants. In this study, we aimed to investigate whether funisitis could affect childhood neurodevelopment. We hypothesized that childhood neurodevelopment would vary across groups with or without funisitis. Material and methods: Using data from the U.S. Collaborative Perinatal Project (1959-1976), 29,725 subjects with available intelligence quotient (IQ) were studied. Detailed placental examinations were conducted according to a standard protocol with quality control procedures. Multivariate logistic regression models were applied to evaluate the relationship between funisitis and IQ at age 4 or 7 years after adjusting for confounders. Results: Early preterm birth children with funisitis had a 3.0-fold (95% confidence interval 1.2, 7.3) risk of low full-scale IQ (<70) at age 4 years, which disappeared until age 7 years. Term birth children with funisitis had 1.9-fold (95% confidence interval 1.2, 3.0) risk of low performance IQ at age 7 years, but they did not have increased risk of low full-scale IQ. No difference in IQ score was found in late preterm birth children. Conclusion: Funisitis may injure the developmental brain of infants, leading to the relative low IQ in early childhood, but the negative effect can be mostly abrogated presumably because of postnatal intentional training.